2015
DOI: 10.1093/molbev/msv049
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism and the Evolution of Sex-Biased Gene Expression in the Brown Alga Ectocarpus

Abstract: Males and females often have marked phenotypic differences, and the expression of these dissimilarities invariably involves sex differences in gene expression. Sex-biased gene expression has been well characterized in animal species, where a high proportion of the genome may be differentially regulated in males and females during development. Male-biased genes tend to evolve more rapidly than female-biased genes, implying differences in the strength of the selective forces acting on the two sexes. Analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
172
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(183 citation statements)
references
References 88 publications
9
172
2
Order By: Relevance
“…Evolutionary rates can be affected by gene expression pattern, in particular breadth of expression [31, 32]. We therefore also compared the dN/dS ratios of sex-linked genes with those of sex-biased genes, because the latter exhibit narrow (sex-specific) expression patterns similar to those observed for SDR genes [33]. Evolutionary rates for SDR genes were comparable to those for sex-biased autosomal genes (Wilcoxon test, p  = 0.19501) but dS values were significantly lower for SDR genes (Wilcoxon test, p  = 0.00017) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Evolutionary rates can be affected by gene expression pattern, in particular breadth of expression [31, 32]. We therefore also compared the dN/dS ratios of sex-linked genes with those of sex-biased genes, because the latter exhibit narrow (sex-specific) expression patterns similar to those observed for SDR genes [33]. Evolutionary rates for SDR genes were comparable to those for sex-biased autosomal genes (Wilcoxon test, p  = 0.19501) but dS values were significantly lower for SDR genes (Wilcoxon test, p  = 0.00017) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although this is somewhat different than work in Drosophila and mammals, where only male-biased genes show elevated rates of evolution (Ellegren and Parsch 2007; Zhang et al 2007; Parsch and Ellegren 2013), it does add to the diversity of patterns observed in other taxa. For example, female-biased genes show more rapid rates of evolution in Neurospora crassa (Whittle and Johannesson 2013), and both male- and female-biased genes show elevated rates of evolution in brown alga (Lipinska et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…It is often assumed that the majority of sexually dimorphic traits arise from differences in expression for genes present in both sexes (Connallon and Knowles 2005; Rinn and Snyder 2005). In line with this, studies in a wide array of organisms have attempted to determine the differences in gene expression between males and females (Parsch and Ellegren 2013), including Drosophila (Assis et al 2012; Perry et al 2014), birds (Pointer et al 2013), nematodes (Albritton et al 2014), and brown alga (Lipinska et al 2015). These works have revealed that a significant fraction of genes in the genome exhibit differential expression between males and females (Rinn and Snyder 2005; Mank, Hultin-Rosenberg, Webster, et al 2008; Reinius et al 2008; Jiang and Machado 2009), which suggests that the expression of sexual dimorphism is related to marked genetic reprogramming (Lipinska et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To compare the EsV-1-7 proteins with known fast-evolving proteins, a similar analysis was then carried out with a set of 905 Ectocarpus sp. sex-biased genes that have one-to-one orthologues in S. japonica (Lipinska et al, 2015). The statistical significance of differences between datasets was evaluated with a Wilcoxon test and bootstrap resampling with replacement (10,000 replicates).…”
Section: Transcriptome Analysismentioning
confidence: 99%